Exploring inclusive innovation: factors influencing interoperability adoption in South Africa's mobile money service provider sector - Zheng, Wenbo (Graduate School of Business (GSB), 2025)
This study investigates the factors influencing the adoption of interoperability among Mobile Money Service Providers (MMSPs) in South Africa, focusing on the implications for financial inclusion and barriers to business-to-business collaboration. Despite the rapid expansion of mobile money platforms, the need for interconnectedness among these services hampers seamless transactions, thereby limiting the overall efficacy of mobile money systems. Using an interpretive philosophy, this research adopts an inductive approach utilising qualitative methodology. A single case study method was implemented, comprising twenty in depth interviews organised into three distinct cohorts to enhance the credibility of the findings. The analysis identified five prominent themes that significantly impact interoperability adoption: Size of the Footprint, User Needs, Degree of Risk and Control, Level of Strategy and Timing, and Profitability. Each theme was critically evaluated for its implications on decision making processes within the MMSP sector, revealing that profitability is a primary motivator for co-opetition among service providers. The findings indicate that although mobile money has the potential to catalyse inclusive innovation, there must be greater clarity between provider priorities and user needs. As such, this research underscores the necessity for greater alignment between academic insights and practical applications in fostering inclusive innovation within the sector. This study developed an inclusive innovation concept model as a potential tool to help refocus inclusive innovation towards a sustainability model.